Logos and Political Order. Representation in the Political Philosophy of Eric Voegelin - Torres, Bernat (ΠΗΓΗ/FONS, 2022)
This article aims to show the anthropological and political relevance of logos or rationality as understood by Eric Voegelin. The paper is divided into two parts, the first elaborates what Voegelin considers to be the discovery of logos by Plato and Aristotle, which represents a historical and at the same time epistemological phenomenon of self-illumination of the human psyche. Through the concept of logos, the human soul is discovered and, with it the political reality can be ordered and organized. The second part of the article focuses on this political dimension of logos or rationality as an element that allows the foundation of political science as it is exposed in Voegelin’s The New Science of Politics (1952), and the concept of political representation as a central element of Voegelin’s political philosophy is explored.
Keywords: Eric Voegelin; Plato; logos; rationality; political philosophy; representation; political representation